PREVALENCE AND CHARACTERISTICS OF PHANTOM LIMB PAIN AND RESIDUAL LIMB PAIN IN CHILDREN AND ADOLESCENTS FOLLOWING UPPER AND LOWER LIMB AMPUTATION (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To report the prevalence of and describe symptoms of PLP and RLP in children and adolescents who have undergone upper and lower limb amputation. Study Design: Cross-sectional study Methods: This study was carried out at Children's Hospital, Lahore from June 2024 to January 2025. Convenience sampling was used to include 245 children and adolescents (6-16 years old) with major limb amputation (at least 6 months after amputation). The Short-Form McGill Pain Questionnaire (SF-MPQ-2) and a demography proforma were used to gather data. The Numeric Rating Scale (children aged 8-16 years) and Faces Pain Scale-Revised (children aged 6-7 years) were used to rate pain intensity. Data were analysed using SPSS (v 26.0). Results: The overall prevalence of PLP was 52.2% (n=128) and RLP was 40.0% (n=98). PLP prevalence increased significantly with age: 41.0% in children aged 6-9 years, 54.1% in children aged 10-12 years, and 63.4% in adolescents aged 13-16 years (χ² = 12.74, p = 0.002). There was no age association for RLP (p = 0.229). RLP did not significantly increase with age (p = 0.229). Aching (17.1%), tingling (16.7%) and throbbing (14.7%) were the most frequent pain descriptors. Pain interfered with mood (68%), sleep (55%) and school (34%). Conclusion: PLP and RLP are commonly reported in children with amputations, with a striking increase in PLP with increasing age. These data require systematic pain assessment and treatment of all children with amputation, taking into account their developmental stage.